The tradition of the Ad familiares and humanist culture: Coluccio Salutati, Niccolò Niccoli, Guarino, the Barzizzas - Reggi, Giancarlo (Ciceroniana On Line, 2024)
The paper analyses the consequences of a collation error in the manuscript now in Florence, BML Plut. 49.9 (IX cent., M) and in its apograph BML Plut. 49.7 (1392, P) for humanist manuscripts (based on a sample of 82 codices out of c. 160 identified). M and P’s descendant humanistic manuscripts are divided into five branches, at the head of which are those of Coluccio Salutati (ς1), Niccolò Niccoli (ς2), Guarino Veronese (ς3), Gasparino Barzizza (ς4), and his son Guiniforte (ς4). Manuscripts in ς1 preserve the dislocation; manuscripts dated from the 1520s in ς2 rebuild book VIII; manuscripts in ς3 delete Caelius’ letters dislocated in book IX; manuscripts in ς4 delete all Caelius’s letters; manuscripts in ς5 move the letters dislocated at the bottom of book VIII. The latter solution is found also in the Milanese incunabula appearing before the Pachel-Scinzenzeler edition of 1480, an edition that conjectured a re-ordering of the letters. Finally, Poliziano (1489) referred to the sequence of M.